2016
DOI: 10.5194/bg-2015-640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High net CO<sub>2</sub> and CH<sub>4</sub> release at a eutrophic shallow lake on a formerly drained fen

Abstract: <p><strong>Abstract.</strong> Drained peatlands often act as carbon dioxide (CO<sub>2</sub>) hotspots. Raising the groundwater table is expected to reduce their CO<sub>2</sub> contribution to the atmosphere and revitalize their function as carbon (C) sink in the long term. Without strict water management rewetting often results in partial flooding and the formation of spatially heterogeneous, nutrient-rich shallow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
(137 reference statements)
1
6
0
Order By: Relevance
“…The CO 2 efflux from the littoral zone of Lochaber is intermediate along the spectrum of exchange rates observed within oligotrophic to hypereutrophic lakes in Finland, which range from 0.004 to 0.814 μmol CO 2 · m −2 · s −1 , respectively (Huttunen et al, ; Repo et al, ). The lake‐atmosphere net CO 2 exchange we observed in the littoral zone of Lochaber Lake was low relative to other more eutrophic systems, such as Lake Soppensee in Switzerland, which releases 0.278 μmol CO 2 · m −2 · s −1 as observed by Eugster et al (), and Polder Zarnekow in Germany, which was found to release 0.566 μmol CO 2 · m −2 · s −1 in a study by Franz et al (). Compared to a global average obtained from 20,632 partial pressure CO 2 measurements performed over 7,939 lakes and reservoirs, the lake‐atmosphere net CO 2 exchange we quantified in the littoral zone of Lochaber Lake was relatively low, as the review of Raymond et al () reported an average exchange rate of 2.812 μmol CO 2 · m −2 · s −1 .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The CO 2 efflux from the littoral zone of Lochaber is intermediate along the spectrum of exchange rates observed within oligotrophic to hypereutrophic lakes in Finland, which range from 0.004 to 0.814 μmol CO 2 · m −2 · s −1 , respectively (Huttunen et al, ; Repo et al, ). The lake‐atmosphere net CO 2 exchange we observed in the littoral zone of Lochaber Lake was low relative to other more eutrophic systems, such as Lake Soppensee in Switzerland, which releases 0.278 μmol CO 2 · m −2 · s −1 as observed by Eugster et al (), and Polder Zarnekow in Germany, which was found to release 0.566 μmol CO 2 · m −2 · s −1 in a study by Franz et al (). Compared to a global average obtained from 20,632 partial pressure CO 2 measurements performed over 7,939 lakes and reservoirs, the lake‐atmosphere net CO 2 exchange we quantified in the littoral zone of Lochaber Lake was relatively low, as the review of Raymond et al () reported an average exchange rate of 2.812 μmol CO 2 · m −2 · s −1 .…”
Section: Resultssupporting
confidence: 52%
“…The shallow water column, metabolism of macrophyte communities, predisposition to surface flows, and often intensified influence of break‐wave action in the littoral zone all encourage enhanced rates of CO 2 exchange relative to the pelagic zone. In terms of CO 2 efflux, the littoral zone can be thought of as an intermediate ecotone between that of a wetland and a pelagic lake ecosystem, with greater carbon processing rates than would be predicted by pelagic nutrient status (Franz et al, ). Relative to the pelagic zone, littoral zone carbon dynamics are thought to be more closely regulated by environmental fluctuations and substrate heterogeneity (Tonetta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the strong and not yet completely understood impact of CH 4 on global warming 4,5 it may seem imprudent to knowingly create or restore an additional source. Furthermore, there is considerable uncertainty on emissions from rewetted peatlands and some studies have reported elevated emissions of CH 4 compared with pristine peatlands [6][7][8][9] .…”
mentioning
confidence: 99%
“…Our ability to interpret CH 4 fluxes in restored wetlands and predict longer term restoration trajectories (Hemes et al, ) is limited by a lack of detailed process studies of restored wetland C cycling under field conditions. Restoration can move wetland ecosystems into new biogeochemical states (Moreno‐Mateos, Power, Comín, & Yockteng, ) and some of these changes are likely to influence CH 4 fluxes, such as eutrophication (Franz, Koebsch, Larmanou, Augustin, & Sachs, ). Though archaeal methanogenesis (Nisbet & Nisbet, ) has been well‐studied in intact wetlands (Bridgham et al, ; Segers, ), the few studies in rewetted peatlands and restored wetlands have focused exclusively on microbial community composition (e.g., Jerman, Metje, Mandić‐Mulec, & Frenzel, ; Putkinen, Tuittila, Siljanen, Bodrossy, & Fritze, ; Urbanová, Bárta, & Picek, ; Wen et al, ) rather than biogeochemical process rates.…”
Section: Introductionmentioning
confidence: 99%